Reformulating Child Custody Determination in Indonesian Islamic Family Law: Realizing the Best Interests of the Child Principle - Age Surya Dwipa Chandra; Mohamad Aniq Aiman Alias (Universitas Islam Negeri Raden Intan Lampung, 2026)
Child custody (ḥaḍānah) determination in Indonesian Islamic family law remains predominantly parent-oriented and has not consistently incorporated the best interests of the child as the primary legal consideration. This challenge is exacerbated by the practice of Religious Courts issuing divorce judgments without explicitly determining child custody when no specific claim is submitted, thereby creating legal uncertainty and weakening the protection of children's rights. This study aims to reformulate the legal framework governing child custody determination within Indonesian Islamic family law to align it with the best interests of the child principle. The research employs a normative juridical method using statutory, conceptual, and analytical approaches to examine legislation, the Compilation of Islamic Law, the Convention on the Rights of the Child, General Comment No. 14 (2013), and relevant legal scholarship. Data were analyzed qualitatively through the perspective of maqāṣid al-sharī‘ah. The findings reveal that the current legal framework remains formalistic, inadequately adopts a child-centered approach, and does not impose an explicit obligation on judges to determine child custody in every divorce judgment. This study proposes a legal reform by positioning child custody determination as an ex officio judicial obligation grounded in the best interests of the child principle and the objectives of maqāṣid al-sharī‘ah. The proposed reform provides a normative foundation for strengthening legal certainty, enhancing children's rights protection, and promoting greater consistency in the adjudication of child custody cases within Indonesia's Islamic family law system.